THE IMPACT OF SEVERE ROAD AND CLIMATIC CONDITIONS ON THE OPERATION OF AUTOMOBILE TIRES (Conferencea, 2024)
The article analyzes the operation of tires of fire and rescue vehicles, tire wear from the impact of an aggressive road surface, influx of thermal shock, road class and climatic conditions. Recommendations are given for calculating the service life of tires for fire and rescue equipments.